Identifikasi Prinsip Fisika Dalam Tari Pa’gellu Toraja - Aris Pulung; Alexander Pakiding; Bergita Gela Saka; Enos Lolang; Silka Silka (Jurnal FisTa : Fisika dan Terapannya, 2024)
This research provides knowledge regarding the existence of physical principles in Toraja pa'gellu dance. This research aims to identify, analyze and describe the physical principles involved in the movements that occur in a pa'gellu dance. The type of research used is qualitative research. Data collection was carried out through observation, documentation and interviews. The location of the research was the lunar dao art studio. The research results show that there are physical principles in pa'gellu dance that need to be known, such as displacement, circular motion, pressure and equilibrium. The movement can be seen from the dancer's initial position to the next position. Circular motion occurs when the dancer rotates around a certain point on one of the toes. Pressure can occur on the soles of the dancer's feet as a cross-sectional area to support the weight of the upper body. Balance can be seen when the dancer cannot balance the body, where when the legs cannot balance the dancer's body can go backwards or forwards and even fall.